PEMIDANAAN DAN PERLINDUNGAN ANAK YANG BERHADAPAN DENGAN HUKUM TINDAK PIDANA KESUSILAAN: STUDI KASUS PUTUSAN NOMOR 30/PID.SUS-ANAK/2016/PN JKT. SEL - Riyadi, Slamet (Jurnal Ilmiah Widya, 2018)
Attention to children has long existed and is in line with human civilization itself, which is growing from day to day. Children are sons of life, the future of the nation and state. The purpose of this study is (1) To find out how the criminal punishment system of children who are faced with the law of decency crime, case study of Decision Number 30 / Pid. Sus-Anak / 2016 / PN South Jakarta. (2) To find out the form of protection and assistance for children who are faced with the law of decency according to Article 59A letter d of Law Number 35 Year 2014 Amendment to Law Number 23 of 2002 concerning Child Protection. The method used is a type of normative juridical research, which is focused on examining the application of rules or norms in positive law. It can be concluded that: (1) In the initial stage, namely the determination of the suspect from the police, then the arrest and detention shall be carried out for a maximum of 7 (seven) days and can be extended by the public prosecutor for 8 (eight) days. (2) The state, the government, regional government, society, and parents or guardians are carried out, responsible for the implementation of child protection by applying diversion and restorative justice for the deliberation process with the police, public prosecutors, judges, correctional institutions, perpetrators and people parents, victims and parents, non-governmental organizations, social services, communities with a full sense of kinship that contains the values ​​of justice restorative to create legal certainty, justice and benefit.